Zanthoxylum armatum DC. extract induces liver injury via autophagy suppression and oxidative damage by activation of mTOR/ULK1 pathway. (15th October 2022) - Huang, Yan; Jiang, Jialuo; Wang, Wenlin; Guo, Jiafu; Yang, Nannan; Zhang, Jian; Liu, Qiuyan; Chen, Yan; Hu, Tingting; Rao, Chaolong
Abstract: Zanthoxylum armatum DC. (ZADC) has anti-inflammatory, antioxidative, and antibacterial effects. The cytotoxicity of methanol extract of Zanthoxylum armatum DC. (MZADC) has been reported for BRL 3 A cell lines. However, whether MZADC can induce liver damage in vivo remains unclear. Therefore, it is essential to explore whether ZADC causes liver injury and, if the results confirm hepatotoxicity, to further study the potential mechanisms for the in-vitro cytotoxicity of the BRL 3 A cell lines. In vivo, different doses (0.346, 0.519, and 1.038 g/kg/day) of MZADC treatment were given by intragastric administration among male Sprague Dawley rats for 28 days. Levels of serum alanine transaminase (ALT), aspartate transaminase (AST), and alkaline phosphatase (ALP) in the high dose group increased. Steatosis and focal necrosis were found in liver cells in rats in the high dose group. In vitro, BRL 3 A cells were cultivated with MZADC at different concentrations (30, 50, and 70 μg/mL) for 24 h. The cell viability, the number of autophagosomes, and the expression levels of LC3 and Beclin-1 were on a decreasing trend. Besides, proportions of p-mTOR/mTOR and p-ULK1/ULK1 increased. Meanwhile, reactive oxygen species (ROS) accumulation and the content of malondialdehyde (MDA) were on the rise while the activity of superoxide dismutase (SOD) and the content of glutathione (GSH) was on the decline. This research suggests that MZADC may cause rats liver injury and inhibit autophagy in BRL 3 A cells by the mTOR/ULK1 pathway, and further induce intracellular oxidative damage. Graphical abstract: Image 1 Highlights: Methanol extract of Zanthoxylum armatum DC. may cause rats liver injury. Elevated levels of alanine transaminase, aspartate transaminase, and alkaline phosphatase in Buffalo Rat Liver-3A cells were observed. Methanol extract of Zanthoxylum armatum DC. may inhibit autophagy in Buffalo Rat Liver-3A cells. Methanol extract of Zanthoxylum armatum DC. may induce intracellular oxidative damage by autophagy suppression.